(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Korean Unlimited BBQ restaurant Samgyupsalamat is owned by YHK F&B Incorporation. The restaurant now has 7 locations; 5 are undergoing restoration and will likely open this year, and more than ten more are planned for Metro Manila in 2018. Samgyupsalamat owner Young Hun Ko donated to DLSU’s scholarship fund. The study reveals that the majority of respondents are female between the ages of 20 and 25 years old, above working student employees at the Korean 199 unlimited samgyup restaurants, with a shift schedule of 9:00 in the morning. The respondents assess the operation management performance in terms of store hours, scheduling, preparation, standardization, reliability, assurance, and empathy. The problems encountered by Korean 199 Unlimited Restaurants in operation management are labor shortages, insufficient training, schedule inflexibility, lack of motivation, lack of communication, little recognition, no potential growth, staff conflict, trust issues, and a lousy manager. The researchers conclude that the employees should have enough skills and knowledge to be effective operation managers based on their performance. The researchers conclude that the two groups of respondents have the same perception of their operation management performance when it comes to the above-mentioned variables. The researchers then concluded that the employees did not mind the attitude of the manager. The researchers recommend that the manager or owner improve their operation management, especially with their employee feedback, appreciate their employee’s good work, and make sure that the appraisal process is a regular, fair, and constructive two-way conversation between your employees. The researchers recommend that the manager and employee follow the guidelines of operation management. An operation team’s mandate is to manage and optimize the processes that keep a business running and generating value. The researchers recommend that the employees follow the guidelines of operation management to improve their performance.